If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(6x + -3) = 120 Reorder the terms: 8(-3 + 6x) = 120 (-3 * 8 + 6x * 8) = 120 (-24 + 48x) = 120 Solving -24 + 48x = 120 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '24' to each side of the equation. -24 + 24 + 48x = 120 + 24 Combine like terms: -24 + 24 = 0 0 + 48x = 120 + 24 48x = 120 + 24 Combine like terms: 120 + 24 = 144 48x = 144 Divide each side by '48'. x = 3 Simplifying x = 3
| 2(1-7x)=114 | | -7(1+2n)=-119 | | 4x^2-10x+5=x-3 | | 6(x+4)-8=24-6x-8+12x | | 6(5k+2)=252 | | 3(x-6)=x+10 | | 3x^2+29x-12= | | 2(7x-4)=2(11+x) | | 0.6x-0.5(11-3x)=-0.8(x-4) | | 12=3m-21 | | x-401.99=149.80 | | 3x=-5y-12 | | -13=2-7b-8 | | 2y-5=5t+4 | | -48-4x=-7x+21 | | -11=1+4k+8k | | 0.10(s+200.00)=55.00 | | -8r+5=29 | | -6m+2m=20 | | 0.10(s+200.00)=100.00 | | -b+2b=3 | | -7+2b+2=-1 | | 15x+1=12x+3 | | 4n-9=2n+10 | | 3w-8=-26 | | 2(n+2)=8-n | | 7p+8p=15 | | -21-6t=27 | | 3a+6a=-9 | | 5y=3x-12 | | 2(x+1)=50 | | (x-1)*(x-2)*(x-3)*(x-4)=(x+1)*(x+2)*(x+3)*(x+4) |